2007
DOI: 10.1111/j.1365-3083.2007.01908.x
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin, a Protein with Cytokine‐like Properties, is Associated with Inflammation in Crohn's Disease

Abstract: In Crohn's disease (CD) mucosal T‐cells produce increased interferon‐γ (IFN‐γ) and tumour necrosis factor‐α (TNF‐α) levels and TNF‐α antibody treatment [Infliximab (Ifx)] is effective. Osteopontin (OPN), a glycoprotein stimulating activated T‐lymphocytes, may be involved in the disturbed immune‐regulation but also in normal immune‐homeostasis and mucosal repair, since it is expressed in many tissues and present in human milk. This study investigates plasma‐OPN levels in CD patients during Ifx treatment and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
50
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 25 publications
2
50
0
3
Order By: Relevance
“…Moreover, soluble OPN may modulate the differentiation and proliferation of CD4 + and CD8 + T cells (Higuchi et al, 2004). Shinohara et al (2005) Recent evidence indicates that plasma OPN levels increase in active Crohn's disease compared with quiescent disease and decline after treatment with the anti-TNF-α monoclonal antibody infliximab (Agnholt et al, 2007). Furthermore, OPN regulates cell-mediated immunity by promoting T cell proliferation and migration as demonstrated in transgenic mice over-expressing OPN; these mice also exhibited an increase in the percentage of CD4 + T cells in lymph nodes (Higuchi et al, 2004).…”
Section: Opn Andmentioning
confidence: 99%
“…Moreover, soluble OPN may modulate the differentiation and proliferation of CD4 + and CD8 + T cells (Higuchi et al, 2004). Shinohara et al (2005) Recent evidence indicates that plasma OPN levels increase in active Crohn's disease compared with quiescent disease and decline after treatment with the anti-TNF-α monoclonal antibody infliximab (Agnholt et al, 2007). Furthermore, OPN regulates cell-mediated immunity by promoting T cell proliferation and migration as demonstrated in transgenic mice over-expressing OPN; these mice also exhibited an increase in the percentage of CD4 + T cells in lymph nodes (Higuchi et al, 2004).…”
Section: Opn Andmentioning
confidence: 99%
“…10 With respect to IBD, Gassler et al first demonstrated increased OPN expression in the terminal ilea of patients with CD. 11 Significant correlations between plasma OPN levels and the disease activities of CD 12,13 and UC 14 have been reported. In the context of UC, we reported a 23.4-fold increase in OPN mRNA expression compared with normal control colon tissues using gene-chip analysis.…”
mentioning
confidence: 99%
“…11,27 In these patients, OPN is produced by gut epithelia, IgG-producing plasma cells, and macrophages. 28,29 Increased OPN expression in areas of active inflammation suggests that OPN is involved in stimulating cytokine production that contributes to a T H 1-predominant adaptive immune response, as is observed in Crohn's disease. 21 Since OPN is also associated with a decrease in the production of the anti-inflammatory cytokine IL-10 by T cells from patients with Crohn's disease, 28 OPN-mediated defects in immune-regulation may further contribute to the development of inflammation.…”
Section: Discussionmentioning
confidence: 99%